Current Perspectives in the Use of Phytotherapy for the Treatment of Breast Cancer - Afiwa Dodzi Anago; Julien A. Gaetan Segbo; Freddy Gnangnon; Casimir D. Akpovi; Clement Agbangla (European Scientific Journal, ESJ, 2023)
Breast cancer is  the most commonly diagnosed cancer leading to death among women worldwide. However, there is a significant improvement in the treatment of breast cancer. Today, the conventional treatment of breast cancer combines surgery , chemotherapy, radiation, targeted therapy, hormone therapy and immunotherapy.  Despite the advances in the diagnosis skills and in the treatment of breast cancer it has been observed that the recurrence rate experienced by breast cancer patients  is quite high. Moreover, the conventional treatment is often accompained with side effects. Thus, there is a need to search for new bioactive molecules.  Plant derived natural compounds can play a major role as sources of new bioactive substances for the treatment of breast cancer. Many plants have been reported to have anti-breast cancer properties. While investigations are being made to demonstrate the cytotoxic activities of many plants, the use of phytomedicine is not generating fully attention by mainstream practitioners. Some significant results were observed by patients with breast cancer history by combining phytotherapy and the conventional medicines.  Hence, plant extracts are more being used   in the treatment of breast cancer as adjuvant therapy. In this review we will present a summary of the advances of the researches on the efficacity of phytotherapeutic products when discussing their use in the treatment of breast cancer.